The Interplay between Oral Microbes and Immune Responses - Al Gebouri, Dr. Hanan Selman Hessan (American Journal of Biology and Natural Sciences, 2025)
Microbes in the oral cavity play significant roles in maintaining an oral balance. However, a balance disorder of the microbial community, termed dysbiosis, also can lead to the development of diseases through various biological processes. Recent advances suggest that an alteration in oral microbiome with chronic inflammation appears to have a pivotal role in the pathogenesis of several diseases. Damaging interactions from host immune responses to microbial antigens could counteract both oral and systemic diseases. In this review, we have discussed the mechanisms by which oral bacteria interface with host systems in the context of localized and systemic inflammatory pathways. Having a further understanding of these mechanisms may suggest new research opportunities, and potentially decipher new therapeutic targets for a biological-based treatment of oral and systemic diseases.